Lie Of The Land : Migrant Workers and the California Landscape - Mitchell, Don, 1961- (Book collections on Project MUSE., 1996)
The beauty of the California landscape is integral to its place in the imagination of generations of people around the world. In The Lie of the Land, geographer Don Mitchell looks at the human costs associated with this famous scenery. Through an account of the labor history of the state, Mitchell examines the material and ideological struggles over living and working conditions that played a large part in the construction of the contemporary California landscape.